Utilization Of Peeled And Unpeeled Pumpkin Flour As A Value-Added Ingredient In Crackers - Anantham, Komathi Chanmal (2013)
The aim of this study is to develop a value-added food from peeled pumpkin pulp flour (PPF) and unpeeled pumpkin pulp flour (UPF) in crackers at substitution levels of 5 %, 10 %, 15 % and 20 % of wheat flour weight. Physico-chemical properties of PPF and UPF were determined with wheat flour as control. The physico-chemical, textural, sensory and storage stability were also investigated for all types of crackers, using 100 % wheat flour crackers as control. PPF and UPF were significantly higher ≤(p0.05) in water holding capacity (WHC) and oil holding capacity (OHC). Significantly high (≤p0.05) ash and crude fibre content together with significantly low (p≤0.05) moisture content and water activity were also observed for PPF and UPF. It was revealed that total dietary fibre (TDF), soluble dietary fibre (SDF) and insoluble dietary fibre (IDF) contents were significantly higher (p≤0.05) in PP F and UPF. Resistant starch (RS), scavenging activity, β-carotene and phenolics content were found to be significantly high (p≤0.05) in PPF and UPF. Mineral content of PPF and UPF were significantly higher (p≤0.05) in calcium and magnesium. Despite significantly low (p≤0.05) in apparent amylose content, PPF and UPF exhibited good pasting profile with significantly low (p≤0.05) pasting temperature, breakdown viscosity and set back value. Significantly high (p≤0.05) final viscosity was also achieved in PPF and UPF.